A estrutura conceitual e epistemológica do comportamento antissocial: uma revisão integrativa - Garcia, Bruno Nogueira (2018)
Antisocial behavior is a polysemic concept that is present in the practice and in the theoretical corpus of areas such as Law, Psychology, Psychiatry and Sociology, assuming a conceptual multiplicity analogous to its various fields of approach. There is no consensus on the nature and dimensionality of antisocial behavior, giving rise to a series of explanatory models of the phenomenon. In this sense, the present study aims to analyze the epistemological organization of theories explaining antisocial behavior. Therefore, it is presented as an integrative literature review, seeking to present and describe the phenomenon, as well as to know and analyze it within its socio-historical context. To construct this review, the APA-PsycArticles, Lilacs and Redalyc databases were selected, as well as the following filters: single descriptor Antisocial Behavior; scientific article type productions; in Portuguese, English and Spanish; in the time period from 2006 to 2016; and in the areas of Human, Social and Health Sciences. The Atlas.ti software (version 5) was used to support the data organization process. A total of 95 articles were selected, detailed as follows: in terms of databases, we obtained 26 articles in APA-PsycArticles, 20 in Lilacs and 49 in Redalyc; in terms of language, there were 35 in English, 38 in Spanish and 22 in Portuguese; in relation to the method, 19 were of a theoretical nature and 76 are empirical studies; in terms of sample, the ones that used children and adolescents in their evaluations were highlighted, with 48.6% of the total empirical studies. After analyzed, the articles were organized according to their epistemological basis, outlining four major approaches: clinical-psychiatric (27 articles), behavioral (28 articles), legal (17 articles) and sociological (23 articles). Each one presented its own thematic axes that were discussed in order to clarify the most prominent approaches to the construct. In the final part of the study, in contrast to the exposed approaches, we presented the integrative models of understanding the phenomenon from a pluralized epistemology. This research constructed a vast epistemological-methodological survey of the models and theories that explain the antisocial behavior, unpublished in Portuguese language, which hopes to serve as reference to studies and works in the multidisciplinary areas for which the theme emerges as a relevant demand.